2011
DOI: 10.1007/s12598-011-0358-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cobalt on structure and properties of TiC0.3N0.7-TiB2 matrix composite ceramics prepared by self-reactive spray forming method

Abstract: In order to improve the structure and properties of TiC 0.3 N 0.7 -TiB 2 composite ceramics produced by self-reactive spray forming, TiC 0.3 N 0.7 -TiB 2 composite ceramics were produced based on the main system of Ti-B 4 C-C (sucrose as the precuror of carbon)-5 wt.%Al, and the cobalt powders with different mass ratios were added. The effects of cobalt on the structure and properties of the ceramic perform samples were studied. The results show that after the addition of cobalt, the main phases of the sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Besides, Ti(C, N) phase shows a small friction coefficient against steels and Ni-based alloys. [166][167][168] Concluding remarks and future plan…”
Section: Mechanical Thermal and Tribological Performance Of Spsed Si3n4 Ceramicsmentioning
confidence: 97%
“…Besides, Ti(C, N) phase shows a small friction coefficient against steels and Ni-based alloys. [166][167][168] Concluding remarks and future plan…”
Section: Mechanical Thermal and Tribological Performance Of Spsed Si3n4 Ceramicsmentioning
confidence: 97%
“…Also Figueiredo et al discussed the tribological behavior of TiCN in ambient air and found that the presence of C–H bonds in the wear track was helpful to achieve low friction during sliding. However, common operations for TiCN are either: (a) to prepare TiCN coating by magnetron sputtering, or (b) to directly add TiCN powder into matrices to fabricate bulk by hot‐pressing sintering . For TiCN coating, the preparation process is multistep and time‐consuming.…”
Section: Introductionmentioning
confidence: 99%
“…These results showed that TiO 2 was an appropriate sintering additive, particularly for mechanical properties. XRD showed that TiO 2 can react with Si 3 N 4 and N 2 to form TiN, thus helping to improve the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%